How does building information modeling influence decision-making process in the project design? An input, process and output analysis - Xavier Morin; Alejandro Romero-Torres (Project Leadership and Society)
Decision-making is critical throughout the entire project cycle, particularly during the project design stage, where the detailed concept is developed based on stakeholders' requirements and project constraints. To improve project design, various digital technologies are employed to provide stakeholders with comprehensive data for informed decision-making. The paper aims to understand how BIM influence the decision-making process – input, decision and output - during the project design. More specifically, we aim to answer the following question: which decision-making challenges could restrict BIM benefits during the project design stage? Utilizing two embedded case studies and a focus group, we explore the perceived benefits and challenges of BIM in decision-making among project actors. This research contributes to the field of digital technologies in project management by highlighting specific benefits and challenges, such as decision validation and the transformation of decision makers’ roles. Our findings illustrate the interconnected nature of these benefits and challenges through the Input-Process-Output model. We specifically emphasize that the advantages of BIM in the decision-making process can be significantly affected if project organizations do not adapt the roles and competencies of decision makers to effectively utilize BIM. The use of BIM therefore brings novel decision-making challenges, which are presented in the discussion.